Self-foreign omphalitis in adult: a case report - Daniel Ardian Soesilo; April Baby (Intisari Sains Medis, 2020)
Introduction: Severe omphalitis in adults is rare and can be caused by both congenital and acquired etiologies. We are reporting an impacted self-foreign-body in omphalitis case induced by accumulated keratin fragments.Case: A 28-year-old overweight male presented with a 3-day history of persistent purulent umbilical discharge with a remittent fever a few days before, constant abdominal tenderness with edema and erythema around navel area. There were no other GIT-related symptoms. He was given oral antibiotics, which showed no improvement. Upon surgery, we examined deep umbilical cavity without urachal connection to the navel. From the umbilical cavity scooped out multiple polypoid umbolith debris. Histopathologic examination revealed pyogenic granuloma with numerous keratin fragments without any foreign bodies.Conclusion: An impacted and infected self-foreign-body may be a cause of omphalitis in adults and could lead to severe and wide-spread infection if left untreated.